Three-dimensional porous Pt / N-MXene catalyst and preparation method thereof
By optimizing the loading of platinum and cluster size, combined with the preparation method of three-dimensional porous Pt/N-MXene catalyst, the problems of high cost and low activity of Pt catalysts are solved, and efficient and stable LOHC dehydrogenation catalytic effect is achieved.
Patent Information
- Application Number
- CN202510078100.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing Pt catalysts have high cost and rarity limitations in the dehydrogenation process of organic liquid hydrogen storage (LOHC), and oxygen-coordinated Pt is prone to form larger particles, resulting in the presence of low-active Pt (IV), affecting the catalytic effect.
By optimizing the loading amount and cluster size of platinum, we ensure that platinum exists in a zero-valent form of high content (more than 80%), the preparation method of three-dimensional porous Pt/N-MXene catalyst is used, including the preparation of sheet MXene, the combination of protonated melamine and MXene, pyrolysis treatment and high-temperature annealing reduction, to form highly dispersed sub-nanoplatin clusters.
The atomic utilization rate of platinum was improved, the stability and activity of the catalyst were significantly enhanced, the catalytic conversion rate of fixed bed was increased to more than 80%, the hydrogen release rate reached more than 600 mmol·gPt-1·min-1, and the conversion rate did not significantly decrease within the reaction time of up to 72 hours.
Smart Images

Figure CN119869590A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and relates to a three-dimensional porous Pt / N-MXene catalyst. The present invention also relates to a method for preparing the three-dimensional porous Pt / N-MXene catalyst. Background Art
[0002] Liquid organic hydrogen storage (LOHC) provides an alternative for the safe storage and transportation of hydrogen. The key to its development lies in optimizing the dehydrogenation process. Methylcyclohexane (MCH) is a typical choice because it is stable at room temperature and pressure, compatible with existing infrastructure, has high hydrogen storage density and low transportation loss. Its catalytic dehydrogenation is a gas-solid multiphase reaction, and its efficiency can be improved by extending the residence time in the catalytic bed. Compared with traditional zero-dimensional catalysts, three-dimensional structured catalysts have richer pore structures, which promote the diffusion and heat transfer of reactants and products, thereby improving the reaction efficiency. Among various active metals (such as Pt, Pd, Rh, Re, Ni and Cu), Pt catalysts show good potential and CH selectivity in LOHC dehydrogenation, but their high cost and rarity limit large-scale application. To overcome this bottleneck, reducing the amount of platinum and optimizing the carrier to improve its utilization efficiency and catalytic performance are feasible strategies.
[0003] MXene is a new type of two-dimensional (2D) transition metal carbide with a high specific surface area. After etching, there are abundant defects on the surface (such as -O, -OH and -F). These defects can serve as anchoring sites for precious metal atoms, especially oxygen sites, which are very effective for the adsorption of platinum cations. However, MXene nanosheets are prone to self-stacking due to high surface energy and strong van der Waals forces between layers, which affects the interfacial charge and microstructure and hinders the effective exposure of anchoring sites. In addition, oxygen-coordinated Pt tends to form larger particles, resulting in the presence of more low-activity Pt (IV), which greatly affects its catalytic effect. How to finely regulate its microstructure and active sites, and conduct structural design and controllable construction of Pt sub-nanoclusters, is still a huge challenge currently faced. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a three-dimensional porous Pt / N-MXene catalyst, which optimizes the platinum loading and cluster size to ensure that platinum exists in a high content (more than 80%) zero-valent form, thereby improving the stability and activity of the catalyst.
[0005] Another object of the present invention is to provide a three-dimensional porous Pt / N-MXene catalyst.
[0006] The first technical solution adopted by the present invention is a method for preparing a three-dimensional porous Pt / N-MXene catalyst, which specifically comprises the following steps: Step 1, preparing MXene sheets; Step 2, preparing a three-dimensional porous N-MXene carrier according to the product obtained in step 1; Step 3, preparing a three-dimensional porous Pt / N-MXene catalyst according to the product obtained in step 3.
[0007] The first technical solution of the present invention is also characterized in that: The specific process of step 1 is: Step 1.1, preparing a LiF / HCl mixed solution; Step 1.2, preparing a sheet MXene according to step 1.1 and the product obtained in step 1.
[0008] The specific process of step 1.1 is: Weigh 1.6-2.4 g of lithium fluoride powder, 15-30 mL of concentrated hydrochloric acid and 5-10 mL of deionized water, pour the lithium fluoride powder, concentrated hydrochloric acid and deionized water into a polytetrafluoroethylene bottle, and heat at 45°C-65°C using a magnetic stirrer to fully dissolve the lithium fluoride powder in the hydrochloric acid to obtain a LiF / HCl mixed solution.
[0009] The specific process of step 1.2 is: 1-1.5 g Ti3AlC2MAX phase powder was added to the LiF / HCl mixed solution, stirred at a speed of 350 rpm-650 rpm, and etched for 24-48 h. After the reaction was completed, the reaction solution was poured into a plastic centrifuge tube, washed with deionized water, centrifuged at a speed of 3500-5500 rpm for 5-15 min, the supernatant was poured off, deionized water was added and centrifuged again, and the supernatant was washed repeatedly until the pH of the supernatant was neutral. The supernatant was discarded, and the precipitate was dispersed in 100 mL-200 mL deionized water and ultrasonically treated in an ice water bath for 2-3 h, and then the dispersion was centrifuged to take the dark green supernatant, which was the single-layer MXene dispersion. The MXene dispersion was freeze-dried for 24-48 h to obtain the lamellae MXene.
[0010] The specific process of step 2 is: Step 2.1, protonating melamine; Step 2.2, preparing a MXene suspension according to the product obtained in step 1; Step 2.3, dispersing the protonated melamine in step 2.1 in deionized water, and then adding it to the MXene suspension prepared in step 2.2. After ultrasonic stirring, the suspension flocculates and precipitates, and then the mixed solution is freeze-dried for 24 to 48 hours to obtain an N-MXene precursor; Step 2.4: Place the freeze-dried N-MXene precursor in a tube furnace, introduce H2 / Ar mixed gas, heat from room temperature to 350°C, store for 10-30 min, and then continue to heat to 550°C for 2-3 h, with a heating rate of 5-10°C / min -1 , and a three-dimensional porous N-MXene support was obtained.
[0011] The specific process of step 2.1 is as follows: 2-4 g of melamine is dispersed in 30-60 mL of anhydrous alcohol, and stirred vigorously for 1.5-2 h, and then 6 mL of concentrated hydrochloric acid is added, and the mixture is mixed and stirred for 2-4 h, and then washed by centrifugation with water and ethanol for 2-5 times, and dried in a vacuum drying oven at 60°C. Finally, the solid is ground into powder to obtain protonated melamine powder.
[0012] The specific process of step 3 is as follows: take 0.3-0.5 g of solid N-MXene carrier, add 20-40 mL of water, add 4-8 mg of H2PtCl6 6H2O, mix and ultrasonicate for 30-60 min, dry at 60℃-80℃ for 12-24 h, put the dried product into a tubular furnace for reduction reaction, introduce H2 / Ar mixed gas, the reduction temperature is 200-500℃; the reduction time is 3-5h; the reduction pressure is 0.1-0.13 MPa, and a three-dimensional porous Pt / N-MXene catalyst is obtained.
[0013] The second technical solution adopted by the present invention is that the three-dimensional porous Pt / N-MXene catalyst is prepared by the preparation method of the three-dimensional porous Pt / N-MXene catalyst.
[0014] The beneficial effect of the present invention is that the present invention prepares highly dispersed sub-nanometer platinum clusters on a nitrogen-doped three-dimensional MXene substrate by a simple impregnation method. The active sites are regulated by introducing doping elements through a non-in-situ doping-pyrolysis method, and the three-dimensional structure of MXene is designed at the same time. The Pt / N-MXene platinum-based catalyst is obtained through freeze-drying, calcination, impregnation, and high-temperature annealing reduction. Not only the atomic utilization of platinum is effectively improved, but also the stability and activity of the catalyst are significantly enhanced. By optimizing the platinum loading and cluster size, it is ensured that platinum exists in a high content (more than 80%) zero-valent form. The fixed bed catalytic conversion rate is increased to more than 80%, and the hydrogen release rate reaches 600 mmol·g Pt -1 ·min -1 As shown above, the conversion rate did not decrease significantly (the decrease rate was less than 1.11%) during the reaction time of 72 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1This is a SEM image of a Pt / N-MXene catalyst sample obtained in Example 1 of the method for preparing a three-dimensional porous Pt / N-MXene catalyst of the present invention; Figure 2 HRTEM image of the Pt / N-MXene catalyst sample obtained in Example 1 of the method for preparing the three-dimensional porous Pt / N-MXene catalyst of the present invention; Figure 3 HRTEM image of the Pt particle size distribution diagram of the Pt / N-MXene catalyst sample obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention; Figure 4 The XPS graph of the Pt / N-MXene catalyst sample obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention shows that Pt 4 f picture; Figure 5 This is a performance diagram of the catalytic dehydrogenation of MCH by the Pt / N-MXene catalyst obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention; Figure 6 XRD diagram of the Pt / N-MXene catalyst obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention before and after catalyzing the dehydrogenation of MCH; Figure 7 This is a Raman graph of the Pt / N-MXene catalyst obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention before and after catalyzing the dehydrogenation of MCH. DETAILED DESCRIPTION
[0016] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0017] The method for preparing three-dimensional porous Pt / N-MXene of the present invention comprises the following steps: Step 1, obtaining MXene sheets; Weigh 1.6-2.4 g of lithium fluoride powder, 15-30 mL of concentrated hydrochloric acid, and 5-10 mL of deionized water. Pour the lithium fluoride powder, concentrated hydrochloric acid, and deionized water into a polytetrafluoroethylene bottle, and heat at 45°C-65°C using a magnetic stirrer to fully dissolve the lithium fluoride powder in the hydrochloric acid (after stirring for 5-10 min) to obtain a LiF / HCl mixed solution; 1-1.5 g Ti3AlC2MAX phase powder (200-400 mesh) was slowly added (addition process 3-5 min) to the LiF / HCl mixed solution. A large number of bubbles were observed in the liquid, indicating that the reaction had started. Stir at a speed of (350 rpm-650 rpm) and etch for 24-48 h. After the reaction was completed, the reaction solution was poured into a plastic centrifuge tube, washed with deionized water, centrifuged at high speed (3500 rpm-5500 rpm) for 5-15 min, the supernatant was poured off, deionized water was added and centrifuged again, and the supernatant was washed repeatedly until the pH of the supernatant was neutral, and the supernatant was discarded. The precipitate was dispersed in 100 mL-200 mL deionized water and treated with ultrasound (200 W-300 W) in an ice water bath for 2-3 h, and then the dispersion was centrifuged. The dark green supernatant was taken, which was the monolayer MXene dispersion. The dispersion was then freeze-dried for 24-48 h to obtain the lamella MXene.
[0018] Step 2, preparing a three-dimensional porous N-MXene support; Preparation of protonated melamine: Disperse 2-4 g of melamine in 30-60 mL of anhydrous alcohol, stir vigorously for 1.5-2 h, and then add 6 mL of concentrated hydrochloric acid. The resulting mixture is further stirred for 2-4 h, then washed by centrifugation with water and ethanol 2-5 times, and dried in a vacuum oven at 60°C. Finally, grind the solid into powder to obtain protonated melamine; A certain amount of protonated melamine was dispersed in deionized water and then added to the prepared MXene suspension (the mass ratio of MXene to protonated melamine was 1:0.5~3). After ultrasonic stirring, the suspension flocculated and precipitated. The mixed solution was then freeze-dried for 24 to 48 hours to obtain the N-MXene precursor. The freeze-dried N-MXene precursor was placed in a tubular furnace, and H2 / Ar mixed gas was introduced, heated from room temperature to 350°C, kept for 10 to 30 minutes, and then continued to heat to 550°C for 2 to 3 hours, with a heating rate of 5 to 10°C⋅min -1 , a three-dimensional porous N-MXene support is obtained; Step 3, preparing a three-dimensional porous Pt / N-MXene catalyst, the specific process is as follows: Take 0.3-0.5 g of solid N-MXene support, add 20-40 mL of water, add 4-8 mg of H2PtCl6 6H2O, after mixing, ultrasonicate for 30-60 min, dry at 60℃-80℃ for 12-24 h, put the dried product into a tube furnace for reduction reaction, introduce H2 / Ar mixed gas, the reduction temperature is 200-500℃; the reduction time is 3-5 h; the reduction pressure is 0.1-0.13 MPa, and a three-dimensional porous Pt / N-MXene catalyst is obtained; The dehydrogenation process of MCH catalyzed by three-dimensional porous Pt / N-MXene is as follows: in a fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are as follows: the temperature of the dehydrogenation reaction is 280-380 °C, the pressure of the dehydrogenation reaction is 0.1-0.5 MPa, and the space velocity of the dehydrogenation reaction is 5-10 h -1 .
[0019] Example 1 Weigh 2.2 g of lithium fluoride powder, 30 mL of concentrated hydrochloric acid, and 10 mL of deionized water. Pour LiF powder, concentrated hydrochloric acid, and deionized water into a polytetrafluoroethylene bottle, heat to 55 °C with a magnetic stirrer, and fully dissolve LiF powder in hydrochloric acid (after stirring for 5 min) to obtain a LiF / HCl mixed solution; slowly (addition process 3 min) add 1.3 g Ti3AlC2MAX phase powder (400 mesh) to the LiF / HCl mixed solution, and a large number of bubbles can be observed in the liquid, indicating that the reaction has begun. Stir at a speed of (350 rpm) and etch for 24 h. After the reaction is completed, pour the reaction solution into a plastic centrifuge tube, wash with deionized water, centrifuge at high speed (3500 rpm) for 5 min, pour off the supernatant, add deionized water and centrifuge again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 100 mL of deionized water and treated with ultrasound (200 W) in an ice-water bath for 2 h, and then the dispersion was centrifuged (5000 rpm) for 1 h. The dark green upper dispersion was taken and freeze-dried for 24 h to obtain flaky MXene.
[0020] 3 g of melamine was dispersed in 40 mL of anhydrous alcohol and stirred vigorously for 1.8 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 3 h, then washed three times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C. Finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to protonated melamine was 1:1), and then added to the MXene suspension (MXene and deionized water suspension), flocculation and precipitation occurred. The mixed solution was then freeze-dried for 24 h to obtain the N-MXene precursor, which was placed in a tubular furnace, and H2 / Ar mixed gas was introduced into the tubular furnace to heat to 350°C, stored for 30 min, and then continued to heat to 550°C for 2 h. The heating rate was 5°C⋅min -1 , and a three-dimensional porous N-MXene support was obtained.
[0021] Take 0.3 g of solid N-MXene support, add 20 mL of water, add 4 mg of H2PtCl6 6H2O, ultrasonic for 30 min, drying at 60℃ for 12 h, the dried product was placed in a tube furnace for reduction reaction, H2 / Ar mixed gas was introduced, the reduction temperature was 350℃, the reduction time was 3 h, and the reduction pressure was 0.1 MPa to obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane were: the dehydrogenation temperature was 350℃, the dehydrogenation pressure was 0.32 MPa, and the weight hourly space velocity of the dehydrogenation was 7.7 h -1 .
[0022] Figure 1 This is a SEM image of the Pt / N-MXene catalyst sample obtained in Example 1. An obvious three-dimensional porous structure can be seen, which confirms the success of the structural design.
[0023] Figure 2 This is a HRTEM image of the Pt / N-MXene catalyst sample obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention. It can be seen that the Pt particles are small and evenly dispersed.
[0024] Figure 3 The HRTEM image of the Pt / N-MXene catalyst sample obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention shows the Pt particle size distribution. After fitting analysis, the average Pt particle size is 1.22 nm. This shows that the active site design is successful, and the formed platinum clusters are highly dispersed and small in size.
[0025] Figure 4 The XPS graph of the Pt / N-MXene catalyst sample obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention shows that Pt 4 fFigure. After fitting and peak analysis, the valence distribution of Pt sub-nanoclusters is mainly Pt (0), which is 80.78%, far better than the results reported in the literature. This is also the main reason for the good dehydrogenation effect of MCH.
[0026] Figure 5 The performance diagram of the Pt / N-MXene catalyst for catalytic dehydrogenation of MCH obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention. It can be seen that during the 72 h reaction, the catalyst maintained good stability and activity, and the conversion rate remained at 80%. Until the end of the reaction, the activity only decreased by 1.1%. Its maximum hydrogen release rate reached 636.30 mmol·g Pt -1 ·min -1 , and never less than 600 mmol·g Pt -1 ·min -1 This also shows that the structural design of the catalyst and the controllable structure of Pt sub-nanoclusters are very important for improving the catalytic activity of MCH.
[0027] Figure 6 The XRD diagram of the Pt / N-MXene catalyst before and after catalyzing the dehydrogenation of MCH obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention. According to the spectrum analysis, the characteristic peaks did not shift or have other peaks, indicating that the properties of the Pt / N-MXene catalyst are very stable during the long-term reaction process.
[0028] Figure 7 The Raman graph of the Pt / N-MXene catalyst obtained in Example 1 of the preparation method of the three-dimensional porous Pt / N-MXene catalyst of the present invention before and after catalyzing the dehydrogenation of MCH. According to the spectrum analysis, for carbon structure materials, the D peak and the G peak are both characteristic peaks of C atomic crystals. The Pt / N-MXene catalyst has a peak at 1358 cm -1 and 1575 cm -1 The characteristic peaks at , correspond to amorphous carbon and graphite carbon, respectively. Their intensity ratio is I D / I G To a certain extent, the defect degree of the reaction material C material has not changed, and no carbon deposition has appeared on the surface, which is consistent with the experimental results, indicating that Pt / N-MXene is an excellent catalyst for long-term stable catalytic dehydrogenation of MCH.
[0029] Comparative Example 1 (When preparing MXene sheets, less than 15 mL of concentrated hydrochloric acid was taken) Weigh 1.6 g lithium fluoride powder, 10 mL concentrated hydrochloric acid, and 5 mL deionized water. Pour the LiF powder and hydrochloric acid solution into a polytetrafluoroethylene bottle, and heat to 55 °C with a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 5 min). Slowly (addition process 3 min) add 1.0 g Ti3AlC2MAX phase powder (400 mesh) to the LiF / HCl mixed solution, and a large number of bubbles can be observed in the liquid, indicating that the reaction has begun. Stir at a speed of (350 rpm) and etch for 24 h. After the reaction is completed, pour the reaction solution into a plastic centrifuge tube, wash with deionized water, centrifuge at high speed (3500 rpm) for 5 min, pour off the supernatant, add deionized water and centrifuge again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 100 mL of deionized water and treated with ultrasound (200 W) in an ice-water bath for 2 h, and then the dispersion was centrifuged (5000 rpm) for 1 h. The dark green upper dispersion was taken and freeze-dried for 24 h to obtain flaky MXene.
[0030] 3 g of melamine was dispersed in 40 mL of anhydrous alcohol and stirred vigorously for 1.8 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 3 h, then washed three times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C. Finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to protonated melamine was 1:1), and then added to the MXene suspension (MXene and deionized water suspension), flocculation and precipitation occurred. The mixed solution was then freeze-dried for 24 h. The obtained N-MXene precursor was heated to 350 ° C in a tube furnace with H2 / Ar mixed gas, kept for 30 min, and then continued to heat to 550 ° C for 2 h. The heating rate was 5 ° C min -1 , and a three-dimensional porous N-MXene support was obtained.
[0031] Take 0.3 g of solid N-MXene support, add 20 mL of water, add 4 mg of H2PtCl6 6H2O, ultrasonic for 30 min, drying at 60℃ for 12 h, H2 / Ar mixed gas reduction temperature of 350℃, reduction time of 3 h, reduction pressure of 0.1 MPa, and Pt / N-MXene catalyst were obtained. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane were: the dehydrogenation temperature was 350℃, the dehydrogenation pressure was 0.32 MPa, and the weight hourly space velocity of the dehydrogenation was 7.7 h -1 .
[0032] Comparative Example 2 (the mass ratio of MXene to melamine is greater than 1:3) Weigh 2.2 g lithium fluoride powder, 30 mL concentrated hydrochloric acid, and 10 mL deionized water. Pour the LiF powder and hydrochloric acid solution into a polytetrafluoroethylene bottle, and heat to 55 °C with a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 5 min). Slowly (addition process 3 min) add 1.3 g Ti3AlC2MAX phase powder (400 mesh) to the LiF / HCl mixed solution, and a large number of bubbles can be observed in the liquid, indicating that the reaction has begun. Stir at a speed of (350 rpm) and etch for 24 h. After the reaction is completed, pour the reaction solution into a plastic centrifuge tube, wash with deionized water, centrifuge at high speed (3500 rpm) for 5 min, pour off the supernatant, add deionized water and centrifuge again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 100 mL of deionized water and treated with ultrasound (200 W) in an ice-water bath for 2 h, and then the dispersion was centrifuged (5000 rpm) for 1 h. The dark green upper dispersion was taken and freeze-dried for 24 h to obtain flaky MXene.
[0033] 3 g of melamine was dispersed in 40 mL of anhydrous alcohol and stirred vigorously for 1.8 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 3 h, then washed three times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C. Finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to protonated melamine was 1:5), and then added to the MXene suspension, resulting in flocculation and precipitation. The mixed solution was then freeze-dried for 24 h, and the obtained N-MXene precursor was heated to 350 °C in a tube furnace with H2 / Ar mixed gas, kept for 30 min, and then continued to heat to 550 °C for 2 h. The heating rate was 5 °C⋅min -1 , a three-dimensional porous N-MXene support was obtained. Take 0.3 g of solid N-MXene support, add 20 mL of water, add 4 mg of H2PtCl6⋅6H2O, ultrasonicate for 30 min, dry at 60℃ for 12 h, reduce with H2 / Ar mixed gas at 350℃, 3 h, and 0.1 MPa to obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are as follows: the temperature of the dehydrogenation reaction is 350℃, the pressure of the dehydrogenation reaction is 0.32 MPa, and the weight hourly space velocity of the dehydrogenation reaction is 7.7 h -1 .
[0034] Comparative Example 3 (N-MXene precursor in a tube furnace, N2 introduced) Weigh 2.2 g lithium fluoride powder, 30 mL concentrated hydrochloric acid, and 10 mL deionized water. Pour the LiF powder and hydrochloric acid solution into a polytetrafluoroethylene bottle, and heat to 55 °C with a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 5 min). Slowly (addition process 3 min) add 1.3 g Ti3AlC2MAX phase powder (400 mesh) to the LiF / HCl mixed solution, and a large number of bubbles can be observed in the liquid, indicating that the reaction has begun. Stir at a speed of (350 rpm) and etch for 24 h. After the reaction is completed, pour the reaction solution into a plastic centrifuge tube, wash with deionized water, centrifuge at high speed (3500 rpm) for 5 min, pour off the supernatant, add deionized water and centrifuge again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 100 mL of deionized water and treated with ultrasound (200 W) in an ice-water bath for 2 h, and then the dispersion was centrifuged (5000 rpm) for 1 h. The dark green upper dispersion was taken and freeze-dried for 24 h to obtain flaky MXene.
[0035] 3 g of melamine was dispersed in 40 mL of anhydrous alcohol and stirred vigorously for 1.8 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 3 h, then washed three times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C. Finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to protonated melamine was 1:1) and then added to the MXene suspension, resulting in flocculation and precipitation. The mixed solution was then freeze-dried for 24 h, and the obtained sample was heated to 350 °C in a tube furnace with N2 gas, kept for 30 min, and then continued to be heated to 550 °C for 2 h. The heating rate was 5 °C min -1 . After annealing, a three-dimensional porous N-MXene support was obtained. Take 0.3 g of solid N-MXene support, add 20 mL of water, add 4 mg of H2PtCl6⋅6H2O, ultrasonicate for 30 min, dry at 60℃ for 12 h, reduce with H2 / Ar mixed gas at 350℃, 3 h, and 0.1 MPa to obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are as follows: the temperature of the dehydrogenation reaction is 350℃, the pressure of the dehydrogenation reaction is 0.32 MPa, and the weight hourly space velocity of the dehydrogenation reaction is 7.7 h -1 .
[0036] Comparative Example 4 (Preparation of three-dimensional porous Pt / N-MXene catalyst using sodium borohydride reduction method) Weigh 2.2 g lithium fluoride powder, 30 mL concentrated hydrochloric acid, and 10 mL deionized water. Pour the LiF powder and hydrochloric acid solution into a polytetrafluoroethylene bottle, and heat to 55 °C with a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 5 min). Slowly (addition process 3 min) add 1.3 g Ti3AlC2MAX phase powder (400 mesh) to the LiF / HCl mixed solution, and a large number of bubbles can be observed in the liquid, indicating that the reaction has begun. Stir at a speed of (350 rpm) and etch for 24 h. After the reaction is completed, pour the reaction solution into a plastic centrifuge tube, wash with deionized water, centrifuge at high speed (3500 rpm) for 5 min, pour off the supernatant, add deionized water and centrifuge again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 100 mL of deionized water and treated with ultrasound (200 W) in an ice-water bath for 2 h, and then the dispersion was centrifuged (5000 rpm) for 1 h. The dark green upper dispersion was taken and freeze-dried for 24 h to obtain flaky MXene.
[0037] 3 g of melamine was dispersed in 40 mL of anhydrous alcohol and stirred vigorously for 1.8 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 3 h, then washed three times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C. Finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to protonated melamine was 1:1) and then added to the MXene suspension, resulting in flocculation and precipitation. The mixed solution was then freeze-dried for 24 h, and the obtained sample was heated to 350 °C in a tube furnace with H2 / Ar mixed gas, kept for 30 min, and then continued to heat to 550 °C for 2 h. The heating rate was 5 °C⋅min -1 . After annealing, a three-dimensional porous N-MXene support was obtained. Take 0.3 g of solid N-MXene support, add 20 mL of water, add 4 mg of H2PtCl6⋅6H2O, ultrasonicate for 30 min, and reduce with sodium borohydride to obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are as follows: the temperature of the dehydrogenation reaction is 350 ° C, the pressure of the dehydrogenation reaction is 0.32 MPa, and the weight hourly space velocity of the dehydrogenation reaction is 7.7 h -1 .
[0038] Table 1 Comparison of dehydrogenation effects of catalysts under different conditions
[0039] As shown in Table 1, the Pt / N-MXene catalyst obtained in Example 1 has the best catalytic effect on the dehydrogenation of MCH. The low concentration of hydrochloric acid in Comparative Example 1 may lead to incomplete etching of the MXene layer, resulting in fewer active sites, and the active sites cannot be further regulated, so the activity is the lowest. The amount of melamine introduced in Comparative Example 2 is more, which means that the more N doping, the weaker the electron-withdrawing ability of N is than O, resulting in a decrease in the ability of the active sites to compete for the adsorption of Pt, the size of the formed Pt clusters is larger, the proportion of high-priced Pt is high, and the catalytic activity becomes lower. In Comparative Example 3, H2 / Ar mixed gas was not used in the preparation of the N-MXene precursor. Under high-temperature annealing conditions, the active sites were not mostly retained, so that the activity of the Pt clusters obtained subsequently was not as good as that under H2 / Ar conditions. However, according to the selectivity of the catalyst, it can be found that they are all higher than 99%, which is due to the excellent CH selectivity of Pt.
[0040] Example 2 Weigh 1.6 g lithium fluoride powder, 15 mL concentrated hydrochloric acid, and 5 mL deionized water, pour the LiF powder, concentrated hydrochloric acid, and deionized water into a polytetrafluoroethylene bottle, and heat to 45°C using a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 8 minutes) to obtain a LiF / HCl mixed solution; 1g Ti3AlC2MAX phase powder (200 mesh) was slowly added (addition process 4min) to the LiF / HCl mixed solution, and a large number of bubbles were observed in the liquid, indicating that the reaction began. Stir at a speed of (450 rpm) and etch for 36h. After the reaction was completed, the reaction solution was poured into a plastic centrifuge tube, washed with deionized water, centrifuged at high speed (4500 rpm) for 10min, the supernatant was poured off, and deionized water was added and centrifuged again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 150 mL deionized water and treated with ultrasound (260W) in an ice water bath for 2.5 h, and then the dispersion was centrifuged (5000rpm) for 1 h. Take the dark green upper dispersion and freeze-dry it for 36 h to obtain flaky MXene.
[0041] 2 g of melamine was dispersed in 30 mL of anhydrous alcohol and stirred vigorously for 1.5 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 2 h, then washed twice by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C; finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to melamine was 1:0.5) and then added to the MXene suspension, resulting in flocculation and precipitation. The mixed solution was then freeze-dried for 36 h to obtain the N-MXene precursor, which was placed in a tubular furnace, and heated to 350 ° C by passing H2 / Ar mixed gas into the tubular furnace, and then kept for 10 min, and then continued to heat to 550 ° C for 2.5 h, with a heating rate of 8 ° C min -1 , and a three-dimensional porous N-MXene support was obtained.
[0042] Take 0.4 g of solid N-MXene support, add 30 mL of water, add 6 mg of H2PtCl6⋅6H2O, ultrasonicate for 40 min, dry at 70℃ for 16 h, put the dried product into a tube furnace for reduction reaction, pass H2 / Ar mixed gas, reduction temperature 200℃, reduction time 4 h, reduction pressure 0.11 MPa, and obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are: the dehydrogenation temperature is 280℃, the dehydrogenation pressure is 0.1 MPa, and the weight hourly space velocity of the dehydrogenation is 5 h -1 .
[0043] Example 3 Weigh 2.4 g lithium fluoride powder, 20 mL concentrated hydrochloric acid, and 8 mL deionized water, pour the LiF powder, concentrated hydrochloric acid, and deionized water into a polytetrafluoroethylene bottle, and heat to 65°C using a magnetic stirrer to fully dissolve the LiF powder in the hydrochloric acid (after stirring for 10 min) to obtain a LiF / HCl mixed solution; 1.5g Ti3AlC2MAX phase powder (300 mesh) was slowly added (addition process 5min) to the LiF / HCl mixed solution, and a large number of bubbles were observed in the liquid, indicating that the reaction began. Stir at a speed of (650 rpm) and etch for 48h. After the reaction was completed, the reaction solution was poured into a plastic centrifuge tube, washed with deionized water, centrifuged at high speed (5500 rpm) for 15min, the supernatant was poured off, and deionized water was added and centrifuged again. Wash repeatedly until the pH of the supernatant is neutral, and discard the supernatant. The precipitate was dispersed in 200 mL deionized water and ultrasonically treated (300W) in an ice water bath for 3 h, and then the dispersion was centrifuged (5000rpm) for 1 h. Take the dark green upper dispersion and freeze-dry it for 48h to obtain flaky MXene.
[0044] 4 g of melamine was dispersed in 60 mL of anhydrous alcohol and stirred vigorously for 2 h, and then 6 mL of concentrated hydrochloric acid was added. The resulting mixture was further stirred for 4 h, then washed five times by centrifugation with water and ethanol, and dried in a vacuum oven at 60 °C; finally, the solid was ground into powder to obtain protonated melamine; 0.3 g of protonated melamine was dispersed in deionized water (the mass ratio of MXene to melamine was 1:3), and then added to the MXene suspension, resulting in flocculation and precipitation. The mixed solution was then freeze-dried for 48 h to obtain the N-MXene precursor, which was placed in a tubular furnace, and H2 / Ar mixed gas was introduced into the tubular furnace and heated to 350 °C, stored for 20 min, and then continued to heat to 550 °C for 3 h, with a heating rate of 10 °C min -1 , and a three-dimensional porous N-MXene support was obtained.
[0045] Take 0.5 g of solid N-MXene support, add 40 mL of water, add 8 mg of H2PtCl6⋅6H2O, ultrasonicate for 60 min, dry at 80℃ for 24 h, put the dried product into a tube furnace for reduction reaction, pass H2 / Ar mixed gas, reduction temperature 500℃, reduction time 5 h, reduction pressure 0.13 MPa, and obtain Pt / N-MXene catalyst. In the fixed bed reactor, the conditions for the dehydrogenation of methylcyclomethane are: the dehydrogenation temperature is 380℃, the dehydrogenation pressure is 0.5 MPa, and the weight hourly space velocity of the dehydrogenation is 10 h -1 .
[0046] Example 4 Compared with Example 1, in step 1, the amount of concentrated hydrochloric acid added is 25 mL, and the remaining steps are the same as in Example 1.
[0047] Example 5 Compared with Example 1, in step 2, the mass ratio of MXene to protonated melamine is 1:2, and the remaining steps are the same as in Example 1.
[0048] Example 6 Compared with Example 1, in step 3, the reduction temperature in the tube furnace is 450° C., and the remaining steps are the same as in Example 1.
Claims
1. A method for preparing a three-dimensional porous Pt / N-MXene catalyst, characterized in that: The specific steps include: Step 1, preparing MXene sheets; Step 2, preparing a three-dimensional porous N-MXene carrier according to the product obtained in step 1; Step 3, preparing a three-dimensional porous Pt / N-MXene catalyst according to the product obtained in step 3.
2. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 1, characterized in that: The specific process of step 1 is as follows: Step 1.1, preparing a LiF / HCl mixed solution; Step 1.2, preparing a sheet MXene according to step 1.1 and the product obtained in step 1.
3. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 2, characterized in that: The specific process of step 1.1 is as follows: Weigh 1.6-2.4 g of lithium fluoride powder, 15-30 mL of concentrated hydrochloric acid and 5-10 mL of deionized water, pour the lithium fluoride powder, concentrated hydrochloric acid and deionized water into a polytetrafluoroethylene bottle, and heat at 45°C-65°C using a magnetic stirrer to fully dissolve the lithium fluoride powder in the hydrochloric acid to obtain a LiF / HCl mixed solution.
4. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 3, characterized in that: The specific process of step 1.2 is as follows: 1-1.5 g Ti3AlC2 MAX phase powder was added to the LiF / HCl mixed solution, stirred at 350 rpm-650 rpm, and etched for 24-48 h. After the reaction was completed, the reaction solution was poured into a plastic centrifuge tube, washed with deionized water, centrifuged at 3500 rpm-5500 rpm for 5-15 min, the supernatant was poured off, deionized water was added and centrifuged again, and the supernatant was washed repeatedly until the pH of the supernatant was neutral. The supernatant was discarded, and the precipitate was dispersed in 100 mL-200 mL deionized water and ultrasonically treated in an ice water bath for 2-3 h. The dispersion was then centrifuged to take the dark green supernatant, which was the single-layer MXene dispersion. The MXene dispersion was freeze-dried for 24-48 h to obtain the lamellae MXene.
5. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 4, characterized in that: The specific process of step 2 is: Step 2.1, protonating melamine; Step 2.2, preparing a MXene suspension according to the product obtained in step 1; Step 2.3, dispersing the protonated melamine in step 2.1 in deionized water, and then adding it to the MXene suspension prepared in step 2.
2. After ultrasonic stirring, the suspension flocculates and precipitates, and then the mixed solution is freeze-dried for 24 to 48 hours to obtain an N-MXene precursor; Step 2.4: Place the freeze-dried N-MXene precursor in a tube furnace, introduce H2 / Ar mixed gas, heat from room temperature to 350°C, store for 10-30 min, and then continue to heat to 550°C for 2-3 h, with a heating rate of 5-10°C / min -1 , and a three-dimensional porous N-MXene support was obtained.
6. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 5, characterized in that: The specific process of step 2.1 is as follows: 2-4 g of melamine is dispersed in 30-60 mL of anhydrous alcohol, and the mixture is stirred vigorously for 1.5-2 h. Then, 6 mL of concentrated hydrochloric acid is added, and the mixture is mixed and stirred for 2-4 h. Then, the mixture is washed by centrifugation with water and ethanol for 2-5 times, and dried in a vacuum drying oven at 60° C. Finally, the solid is ground into powder to obtain protonated melamine powder.
7. The method for preparing the three-dimensional porous Pt / N-MXene catalyst according to claim 6, characterized in that: The specific process of step 3 is as follows: take 0.3-0.5 g of solid N-MXene carrier, add 20-40 mL of water, add 4-8 mg of H2PtCl6 6H2O, mix and ultrasonicate for 30-60 min, dry at 60℃-80℃ for 12-24 h, put the dried product into a tubular furnace for reduction reaction, introduce H2 / Ar mixed gas, the reduction temperature is 200-500℃; the reduction time is 3-5 h; the reduction pressure is 0.1-0.13 MPa, and a three-dimensional porous Pt / N-MXene catalyst is obtained.
8. A three-dimensional porous Pt / N-MXene catalyst, prepared by the preparation method of the three-dimensional porous Pt / N-MXene catalyst according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nitrogen-doped porous carbon-coated metal nano composite catalyst and preparation method thereof
CN111013624A
Preparation method of MXene and porphyrin cellulose nanocrystalline composite film
CN113943437A
Preparation method of methylcyclohexane dehydrogenation catalyst platinum-based manganese-titanium dioxide
CN117899863A
Preparation method and application of three-dimensional oxygen-vacancy-enriched nitrogen-doped Ti3C2TxMXene-loaded CuNi alloy
CN118048645A
Preparation method and application of Pd-based alloy supported catalyst
CN118507744A
Cited By
Preparation method of aerogel heterogeneous catalyst with temperature response
CN121372522A